A penile fracture hidden behind a urethral bleeding - Pedro Francisco Fernandes; Ana Marta Ferreira; Paulo Azinhais; Arnaldo Figueiredo (Urology Case Reports, 2023)
Penile fracture with urethral injury is uncommon. Diagnosis is usually based on clinical history and physical examination. Nonetheless, atypical presentation obliges complementary examinations to be performed.We report a case of a 45-years-old man with urethral bleeding after a blunt penile trauma that was ultimately diagnosed as having a cavernous body laceration on top of an urethral rupture.